Place branding : global, virtual and physical identities, constructed, imagined and experienced - Govers, Robert, ....-; Go, Frank, ....- (New York : Palgrave Macmillan, 2009)
How will places continue to compete for the attention of potential investors, migrant workers, traders, students or tourists in an overcrowded, globalised and increasingly online market? This book provides a new perspective on the subject of Place Branding. In particular, it capitalizes on gaps across the virtual and physical global economy and builds a comprehensive and structured overview of the relevant principles, philosophies, fundamentals and models. Beyond logos and slogans, spin and gloss, it links concepts of place identity, projected image, product offering, consumption experience and perceived image in full coverage and in an orderly, theoretically modelled manner, dividing the book into relevant parts and chapters. Each part consists of a theoretical chapter and relevant research based case studies. A unique, recurring and scrupulously analyzed, best-practice, signature case study is Dubai, but also examined are Flanders (Belgium), Florida, Morocco and Singapore, the Canary Islands, The Netherlands (and its province of Zeeland), and Wales. The concluding part of the book then provides a practical, but comprehensive model that guides practitioners, students and researchers in the application of place branding.
Keywords: Markenartikel; Marketing; Place branding; Place marketing -- United Arab Emirates -- Dubai -- Case studies; Place marketing; Standortmarketing; Tourism -- Marketing; Tourism -- United Arab Emirates -- Dubai -- Case studies